Evaluation of the Implementation of Productive Zakat to Improve the Welfare of Mustahik at Baznas of Bulungan Regency - Robi; Widana, IGN Oka (Ilmu Ekonomi Manajemen dan Akuntansi, 2026)
This study aims to evaluate the implementation of the productive zakat program in improving the welfare of mustahik at the National Amil Zakat Agency (BAZNAS) of Bulungan Regency, by analyzing the role of business assistance and income improvement. A quantitative approach using a survey method was applied to 100 mustahik recipients of productive zakat, selected purposively. Data collection was carried out using questionnaires, and data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) using SmartPLS 3.0. The results of the study indicate that productive zakat has a positive and significant effect on the welfare of mustahik. Income improvement is proven to be the strongest predictor of welfare, while business assistance has the most significant effect on income improvement itself. Furthermore, income improvement acts as a significant full mediator in the relationship between business assistance and welfare. Further. These findings conclude that the effectiveness of productive zakat is highly dependent on the quality of guidance. Therefore, the main recommendation for zakat administrators is to reorient strategies from merely distributing funds (financial injection) toward strengthening a comprehensive guidance system (capacity building) to create a sustainable empowerment impact. The purpose of this study is to analyze the effectiveness of productive zakat programs in improving the welfare of mustahik, by tracing the causal role of business mentoring and income enhancement variables. The findings of this study are expected to provide empirical contributions for more effective and sustainably impactful zakat management.